Voyaging Through Uncharted Territories: A Phenomenological Study of Elementary Education Amidst the New Normal - Magbanua, Yehlen S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
As the world slowly recovers from the COVID-19 pandemic, it is clear that we will not be returning to the world we once knew. Instead, we are adapting to a "New Normal" - a world where we must learn to coexist with the virus. This new way of life vastly differs from what we were accustomed to, and every aspect of our lives has been impacted. Teachers have a significant role in shaping the future of education, and they, too, have been affected by the pandemic. In this study, we sought to understand the challenges and issues public elementary school teachers face in the Philippines due to the pandemic. We employed a qualitative phenomenological research design, selecting nine participants who shared their experiences. Through our analysis, we identified seven themes, including lack of communication, parents' low levels of education, insufficient time for printing modules, teachers' out-of-pocket expenses, difficulty in assessing learners' academic performance, the need for professional growth, and teachers' positive response to the changes. Despite their challenges, these teachers remain resilient and motivated to adapt to the new normal. Despite the difficulties, they continue to work hard to ensure their pupils receive quality education.